Bruns Field International Group / Muhammad Zharif Suhaimi - Suhaimi, Muhammad Zharif (Faculty of Business and Management, 2023)
This is a report on an industrial training program for undergraduate students. The industrial training is expected to be completed within the university's timeframe of February 27, 2023 to August 11, 2023. The goal of industrial training is to expose students to the real-world work environment in the field or industry connected to the course they are taking. In my internship report, I will go through the experiences I had and the things I learned during my six months of internship. I choose Bruns Field International Group as my host organization to do my internship. Bruns Field International Group is a diversified multinational corporation with its headquarters in Malaysia. Founded in 1982, the company has emerged as a prominent player in various sectors, including real estate development, construction, engineering, infrastructure, and hospitality. I also outline the responsibilities that were assigned to me in this report. This assignment provided me with a lot of exposure, experience, and information. This report also discusses the firm, the benefits offered, what I received, and any recommendations that may be made based on my observations throughout the internship periods. Bruns Field International Group has continually showed outstanding financial performance, with stable revenue growth and a strong financial position. Prudent financial management and an emphasis on operational efficiency have contributed to the company's long-term profitability. Last, but not least, experience has been the most useful thing for me during my one-semester training term since it has prepared me for working in the sector on a good day. In many respects, this experience has been beneficial to me. My internship enables me to view things from a range of viewpoints. Every internship experience will be beneficial in the future when working in the real world. Additionally, an internship experience develops my independence. My internship has also helped me to become a better communicator and sociable person.